Rapid and simple determination of psychotropic phenylalkylamine derivatives in urine by direct injection liquid chromatography–electrospray ionization–tandem mass spectrometry. (25th April 2012) - Kwon, Woonyong; Kim, Jin Young; Suh, SungIll; In, Moon Kyo
ABSTRACT: A direct injection liquid chromatography–electrospray ionization–tandem mass spectrometric method (LC‐ESI‐MS/MS) was developed and validated for the rapid and simple determination of 13 phenylalkylamine derivatives. Eight deuterium‐labeled compounds were prepared for use as internal standards (ISs) to quantify the analytes. Urine samples mixed with ISs were centrifuged, filtered through 0.22 µm filters and then injected directly into the LC‐ESI‐MS/MS system. The mobile phase was composed of 0.2% formic acid and 2 mM ammonium formate in distilled water and 0.2% formic acid and 2 mM ammonium formate in acetonitrile. The analytical column was a Capcell Pak MG‐II C18 (150 × 2.0 mm i.d., 5 µm, Shiseido). Separation and detection of the analytes were accomplished within 10 min. The linear ranges were 5–750 ng/mL (ephedrine and fenfluramine), 10–750 ng/mL (3, 4‐methylenedioxyamphetamine, phendimetrazine, methamphetamine, 3, 4‐methylenedioxyethylamphetamine and benzphetamine), 20–750 ng/mL (norephedrine, amphetamine, phentermine and ketamine) and 30–1000 ng/mL (3, 4‐methylenedioxymethamphetamine and norketamine), with determination coefficients, R 2, ≥ 0.9967. The intra‐day and inter‐day precisions were within 19.1%. The intra‐day and inter‐day accuracies ranged from −16.0 to 18.7%. The lower limits of quantification for all the analytes were lower than 26.5 ng/mL. The applicability of the method was examined by analyzing urine samples from drug abusers ( n = 30). Copyright © 2012 John Wiley & Sons, Ltd.